Interplay between GST and nitric oxide in the early response of soybean (Glycine max L.) plants to salinity stress - Dinler, Burcu Seckin Eckin; Antoniou, Chrystalla; Fotopoulos, Vasileios (My University, 2014)
Glutathione-s-transferases (GSTs) and nitric oxide (NO) have both been implicated in the response of plants to salinity stress. However, their interplay and underlying mechanisms are relatively unknown. The present study attempts to provide new insight into the time course effects of NO application on GST biosynthesis regulation in Glycine max L. leaves under salt stress. A 150 μM concentration of sodium nitroprusside (SNP), a widely used NO donor, was sprayed on soybean seedlings for two days at 24 h intervals, followed by application of 200 mM NaCl. The relative water content (RWC), total chlorophyll content (CHL), stomatal conductance (gs), ABA content, malondialdehyde (MDA), hydrogen peroxide content (H2O2), along with GST enzyme and isoenzyme activities and GST1 and GST4 transcript levels were determined at 0 h, 6 h and 12 h after stress imposition. The results indicated that salt treatment alone did not alter MDA, H2O2 or ABA content and stomatal conductance in soybean leaves, most likely due to short-term (6 h and 12 h) application, although lower RWC and CHL were recorded. SNP treatment alone increased ABA content and reduced stomatal conductance, but did not change RWC, CHL, MDA (except at 12 h) and H2O2. However, exogenous SNP application protected soybean leaves from salt stress by increasing RWC, CHL and ABA content, as well as by lowering stomatal conductance in order to maintain water balance. A significant increase in GST activity was recorded under salt stress alone at 6 h. Conversely, SNP application lowered GST activity in soybean leaves at 0 h and 12 h, while it increased at 6 h, supported by GST isoenzyme activities. Thus, it could be suggested that exogenous NO application induced GST activity in an ABA-dependent manner, while GST activity could also be induced by salt stress independent of ABA. In addition, SNP pre-treatment in salt-stressed seedlings lowered GST activity at 6 h and 12 h, in line with the GST isoenzyme expression profile. Finally, GST1 and GST4 transcript levels were significantly induced in both salt-stressed and SNP pre-treated and subsequently stressed samples at 6 h and 12 h, while a more variable regulation pattern was observed in plants treated only with SNP. Overall, our findings suggest that both NO and salt stress act as potent regulators of GST gene and enzyme expression through both ABA-dependent and independent pathways.
Keywords: Nitric oxide; Glutathione-s-transferase; Abscisic acid; Salt stress; Soybean